FINTECH ON MSMEs PERFORMANCE IN BANDA ACEH - Syarifah, Raudzah; Alfarisi, Mohamad Fany; Rahim, Rida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to analyze the impact of financial technology (Fintech) on the performance of micro, small, and medium enterprises (MSMEs) in Banda Aceh City. The Unified Theory of Acceptance and Use of Technology (UTAUT) model is used as the theoretical framework in this study. The variables studied include performance expectancy, effort expectancy, social influence, and facilitating conditions. The research method used is Structural Equation Modeling (SEM) with SmartPLS 4.0. Data were obtained through questionnaires distributed to 150 MSME actors in Banda Aceh. The results showed that performance expectancy and facilitating conditions positively and significantly affected MSMEs' use of fintech. However, effort expectancy had a negative and insignificant impact on fintech utilization. Social Influence had a positive but insignificant effect on the use of fintech. Fintech had a positive and significant impact on the performance of MSMEs. This research implies that the government needs to improve facilities and technological support for MSMEs and provide more intensive training and education related to fintech utilization to improve MSME performance. This study also suggests that future researchers can consider other variables that may affect the use of fintech by MSMEs.